2005
DOI: 10.1103/physreva.71.054302
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic implementation of a nonlocal operation using a nonmaximally entangled state

Abstract: We develop the probabilistic implementation of a nonlocal gate exp [iξσn A σn B ] and ξ ∈ [0, π 4 ], by using a single non-maximally entangled state. We prove that, nonlocal gates can be implemented with a fidelity greater than 79.3% and a consumption of less than 0.969 ebits and 2 classical bits, when ξ ≤ 0.353. This provides a higher bound for the feasible operation compared to the former techniques [9,14,16]. Besides, gates with ξ ≥ 0.353 can be implemented with the probability 79.3% and a consumption of 0.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Minor and fairly obvious changes are all that is needed to extend the discussion from rank 1 to projectors P j of general rank in (9). First, the controlled-X j gates in Figs.…”
Section: Generalization To Projectors P J Of Higher Rankmentioning
confidence: 99%
See 3 more Smart Citations
“…Minor and fairly obvious changes are all that is needed to extend the discussion from rank 1 to projectors P j of general rank in (9). First, the controlled-X j gates in Figs.…”
Section: Generalization To Projectors P J Of Higher Rankmentioning
confidence: 99%
“…By inverting the transform in (50) the P k can be written as linear combinations of the U (j ), allowing (9) to be rewritten in the form (18). Since in this case G is cyclic of order N , it is evident that the two protocols require the same entanglement and communication resources.…”
Section: E Relationship To Controlled Unitariesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been proved that one Bell state can be used to implement arbitrary controlled-rotations on two separate qubits [7,8,12] . If the used entangled state is not maximally entangled, the known protocols can only succeed with some probability [13][14][15][16] . Though sometimes the protocols will fail, Duan and co-workers [17] showed that effective quantum computation can still be achieved.…”
Section: Nonlocal Gate Implementation Using Entanglementmentioning
confidence: 99%